Application of multicriteria decision methods in restoration of buildings in the old town/Daugiakriterinių metodų taikymas vertinant senamiesčio pastatų renovacijos investicinius projektus - Ustinovičius, Leonas; Jakučionis, Sigitas (Journal of Civil Engineering and Management, 2000)
The largest part of old towns in Lithuania are to be regenerated. Sociological evaluation made in 1998 in Vilnius showed that the main problem of the Old Town are falling buildings. Nowadays investment into real estate is evaluated according to a single criterion. That’s why it is so complicated to review the whole investment process. The object under investigation is the buildings in Vilnius Old Town. Condition of building constructions was evaluated. The location of building and possibilities of building usage are being € evaluated also. Vilnius real estate market data was collected from Vilnius general plan. Values of building at various stages of reconstruction are calculated. There are 5 different alternatives of marketing. The scheme of building marketing is presented in Fig 2. There are schedules of the reconstruction work made (Figs 3 and 4). An estimation of different alternatives of building reconstruction is calculated (Table 3). Alternatives of building regeneration were evaluated in accordance with 14 criteria: profit of the project, life-time of building, price of the maintenance, perspectives of business, comfortability of building, price of building sale, insulation, possible losses because of accidents, cost of the building acquiring and reconstruction, location of building, price of the rent, term from the building acquiring till realisation, place for car parking and appearance. Decision matrix is presented in Table 4. Rationality of alternatives was calculated using TOPSIS method. Ranking of alternatives is presented in Table 5. We suppose that multi-criteria evaluation of the investment options creates new possibilities for investors and helps to choose the best variant of the building usage. Article in Lithuanian. First Published Online: 26 Jul 2012